Serum Concentrations of Vascular Endothelial Growth Factor and Monocyte-Colony Stimulating Factor in Peripheral Arterial Disease - Ikeda, Uichi; Matsui, Keiji; Murakami, Yoshiaki; Yoshioka, Toru; Takahashi, Masafumi; Shimada, Kazuyuki (Circulation Journal, 2003)
Vascular endothelial growth factor (VEGF) strongly promotes angiogenesis, and monocyte-colony stimulating factor (M-CSF) regulates the differentiation, proliferation, and survival of monocytes. Both VEGF and M-CSF are expressed in atherosclerotic lesions. The present study was performed to clarify the role of VEGF and M-CSF in the development of peripheral artery disease (PAD). The serum VEGF and M-CSF concentrations were determined in patients with arteriosclerosis obliterans (ASO) and thromboangitis obliterans (TAO). In both patient groups the serum VEGF concentrations were significantly higher than those in the control subjects. In contrast, the serum M-CSF concentrations in the ASO patients were significantly higher than those in both the TAO patients and control subjects, but there were no differences in the M-CSF concentrations between the TAO patients and control subjects. There was no correlation between the serum concentrations of VEGF and M-CSF. In conclusion, the serum VEGF concentration was increased in ASO and TAO patients, but increased concentration of M-CSF was seen only in ASO patients. These results may reflect a difference between ASO and TAO in disease pathogenesis. (Circ J 2003; 67: 660 - 662)